2014
DOI: 10.1007/s10534-014-9724-9
|View full text |Cite
|
Sign up to set email alerts
|

The bioavailability of different zinc compounds used as human dietary supplements in rat prostate: a comparative study

Abstract: The normal human prostate accumulates the highest levels of zinc (Zn) of any soft tissue in the body. The pool of zinc available to the body is known to significantly decrease with age. It is suggested that dietary Zn supplementation protects against oxidative damage and reduces the risk of cancer. Zinc sulfate and zinc gluconate were the most frequently mentioned in per os administration in studies on Zn supplementation. The major aim of the study was to compare the bioavailability of different Zn compounds (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The zinc compound used for supplementation was selected on the basis of the outcome of an earlier study [15], in which zinc gluconate was found to exhibit the highest bioavailability in the rat prostate. After conversion, the applied zinc and selenium doses corresponded to the average level of recommended dose for supplementation in humans.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The zinc compound used for supplementation was selected on the basis of the outcome of an earlier study [15], in which zinc gluconate was found to exhibit the highest bioavailability in the rat prostate. After conversion, the applied zinc and selenium doses corresponded to the average level of recommended dose for supplementation in humans.…”
Section: Methodsmentioning
confidence: 99%
“…The prostate was divided into dorso-lateral (DL) and ventral (V) lobes as described previously [15]. The tissues were stored at −80 °C in cryo-tubes for further analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…to their diet for 30 days. Only zinc gluconate and zinc citrate increased the zinc concentrations in the dorsolateral lobe of the prostate compared to controls 54 . In addition, Wegmüller et al used the double-isotope tracer method with 67 Zn and 70 Zn, and found that the median (IQR) fractional absorption of zinc from zinc oxide (49.9%) was significantly lower than that from zinc citrate (61.3%) and zinc gluconate (60.9%), but there was no marked difference between two organic zinc sources 55 .…”
Section: Discussionmentioning
confidence: 74%
“…The animals in the DSZ group received Zn sulfate supplementation and the animals in the DGZ group received Zn gluconate supplementation, both compounds orogastrically administered at a dose of 15 mg/kg body weight/day once daily for 4 weeks (Sapota et al, 2014). The dose choice used complied with the recommended maximum limit for rodents (National Academy of Sciences, 2001) and humans (Institute of Medicine, 2002) and it was calculated for each compound as a whole.…”
Section: Zinc Supplementationmentioning
confidence: 99%